The dark triad and corporate sustainability: An empirical analysis of personality traits of middle managers - Pelster, Matthias; Schaltegger, Stefan (Business Ethics, the Environment & Responsibility)

Digital Transformation - Towards flexible human-centric enterprises - Kehrbusch, Burkhard; Engels, Gregor (Digital Transformation: Core Technologies and Emerging Topics from a Computer Science Perspective)

Optimization of optical waveguide antennas for directive emission of light - Farheen, Henna; Leuteritz, Till; Linden, Stefan; Myroshnychenko, Viktor; Förstner, Jens (Journal of the Optical Society of America B)
Optical traveling wave antennas offer unique opportunities to control and selectively guide light into a specific direction, which renders them excellent candidates for optical communication and sensing. These applications require state-of-the-art engineering to reach optimized functionalities such as high directivity and radiation efficiency, low sidelobe levels, broadband and tunable capabilities, and compact design. In this work, we report on the numerical optimization of the directivity of optical traveling wave antennas made from low-loss dielectric materials using full-wave numerical simulations in conjunction with the particle swarm optimization algorithm. The antennas are composed of a reflector and a director deposited on a glass substrate, and an emitter placed in the feed gap between them serves as an internal source of excitation. In particular, we analyze antennas with rectangular- and horn-shaped directors made of either hafnium dioxide or silicon. The optimized antennas produce highly directional emissions due to the presence of two dominant guided TE modes in the director in addition to leaky modes. These guided modes dominate the far-field emission pattern and govern the direction of the main lobe emission, which predominately originates from the end facet of the director. Our work also provides a comprehensive analysis of the modes, radiation patterns, parametric influences, and bandwidths of the antennas, which highlights their robust nature.
Keywords: tet_topic_opticalantenna

Dear Guests, please pay for my license – Analyzing the heterogenous cost-pass-through of commercial and non-commercial rental suppliers in response to regulatory policies - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Moment or Movement – An Empirical Analysis of the Heterogeneous Impact of Media Attention on Charitable Crowdfunding Campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Numerical analysis of the coherent mechanism producing negative polarization at backscattering from systems of absorbing particles - Alhaddad, Samer; Grynko, Yevgen; Farheen, Henna; Förstner, Jens (Optics Letters)
We study a double-scattering coherent mechanism of negative polarization (NP) near opposition that is observed for powder-like surfaces. The problem is solved numerically for absorbing structures with irregular constituents, cubes, spheres, and ellipsoids larger than the wavelength of incident light. Our simulations show that double scattering between two random irregular particles shows weak NP. Adding one more particle significantly increases the relative contribution of double scattering which enhances NP. Simulations with regular shapes and controlled geometric parameters show that the interference mechanism is sensitive to the geometry of the scattering system and can also result in no polarization or even strong enhancement of positive polarization at backscattering.
Keywords: tet_topic_scattering

Utilizing Geographic Information Systems for Condition-Based Maintenance on the Energy Distribution Grid - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Context in Design Science Research: Taxonomy and Framework - Herwix, Alexander; zur Heiden, Philipp (Proceedings of the 55th Hawaii International Conference on System Sciences)

A Renaissance of Context in Design Science Research - zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Introduction to the Data-driven Services in Manufacturing Minitrack - Exploring Management, Engineering, and Organizational Transformation - Koldewey, Christian; Dumitrescu, Roman; Rabe, Martin (Proceedings of the 55th Hawaii International Conference on System Sciences)